Inertial Flywheel Resistance Training in Tendinopathy Rehabilitation: A Scoping Review - Ian Burton; Aisling McCormack (North American Sports Medicine Institute, 2022)
# Background Inertial Flywheel Resistance Training (IFRT) has recently emerged as a beneficial rehabilitation option for some musculoskeletal disorders. Although the use of resistance training as treatment for tendinopathy has become widespread, it is unclear if IFRT has efficacy as a treatment option for tendinopathies. # Objective To identify current evidence on IFRT in the treatment of tendinopathy, evaluating intervention parameters and outcomes. # Methods This scoping review was reported in accordance with the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Databases searched included MEDLINE, CINAHL, AMED, EMBase, SPORTDiscus, Cochrane library (Controlled trials, Systematic reviews), and five trial registries. Two independent reviewers screened studies at title, abstract and full text. Following screening, data were extracted and charted, and presented as figures and tables alongside a narrative synthesis. Any study design conducted on adults, investigating the effects of IFRT for tendinopathy were included. Data were extracted on intervention parameters and outcomes of IFRT interventions. # Results Four studies on patellar tendinopathy were included. A variety of outcomes were assessed, including pain, function, strength, power, and tendon morphological and mechanical properties, particularly changes in tendon thickness. IFRT intervention parameters were largely homogenously prescribed, with slight variances. # Conclusion Despite a paucity of studies to date on the effects of IFRT for treating tendinopathy, preliminary evidence for beneficial effects of IFRT on clinical outcomes in patellar tendinopathy is encouraging. As IFRT is a relatively new and unexplored method in tendinopathy rehabilitation, definitive conclusions, and recommendations cannot be made at present, which should be addressed in future research, due to the potential therapeutic benefits highlighted in this review.